Problems of legal regulation of trade of veterinary drugs through the example of “Trifuzol” - Anischenko, M. A.; Parchenko, V. V.; Alekseev, O. H.; Hamburh, I. A.; Hunchak, A. V.; Gutyj, B. V.; Аніщенко, Михайло Анатолійович; Парченко, Володимир Володимирович; Алексєєв, Олександр Германович (India, 2019)
In this article, the issues of legal regulation of veterinary pharmacy were covered based on the actual Ukrainian law, management of similar issues in foreign countries and international guidelines were analyzed, problems of trade of veterinary drugs on the market were studied through the example of veterinary medicine “Trifuzol,” new suggestions regarding the amendments in laws that control the sales of veterinary drugs were developed.
Keywords: trifuzol; veterinary drugs